Standing in the Doorway: Representations and Realities of Punjabi International Students in Canada - Marom, Lilach; Fontaine, Paul; Brunner, Lisa Ruth; Chhina, Gagun (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
This article examines the construction of international students, particularly Punjabi international students, in Canadian policies and mainstream media discourses post–COVID-19. It then juxtaposes these representations with the perspectives of students themselves, as captured through a survey with Punjabi international students transitioning out of British Columbia colleges and teaching universities. Our analysis reveals the fraught dialectic between the policy landscape, media discourses, and Punjabi international students’ trajectories. On a policy level, when international students are perceived to hold high economic value with low social costs, they are welcomed; when that perception shifts, they are “Othered.” Similarly, media discourses represent Punjabi international students in complex and often contradictory ways as victims, system abusers, commodities, and strains on infrastructure. In contrast, Punjabi international students largely see themselves as young people striving to build better futures, buying into the “Canadian dream” while simultaneously navigating processes that render them vulnerable to exploitation and Othering.